Henry James goes to the movies - Griffin, Susan M., 1953- (The University Press of Kentucky, 2015)
Why has a nineteenth-century author with an elitist reputation proved so popular with directors as varied as William Wyler, François Truffaut, and James Ivory? A partial answer lies in the way many of Henry James's recurring themes still haunt us: the workings of power, the position of women in society, the complexities of sexuality and desire. Susan Griffin has assembled fifteen of the world's foremost authorities on Henry James to examine both the impact of James on film and the impact of film on James. Anthony Mazella traces the various adaptations of The Turn of the Screw, from novel to pl.